A Cross Sectional On Leukocytes, Blood Glucose, Cholesterol, Triglyceride, Temperature, Onset, Comorbidities, Sex, And Benson's Relaxation Response - Dwi Mulianda; Endro Haksara (LPPM STIKes Karya Kesehatan, 2021)
Abstract. The increase in physiological response may lengthen ischemic duration, cause recurrent stroke risk and worsen the complication of AIS (Acute Ischemic Stroke) attack which results in impairment and death. The identification of AIS patients with the risk of increasing physiological response is essential during treatments in hospitals. Some of the factors related to the increase of physiological response had been identified, yet the factors that include the intervention remain unknown. The factors are leukocyte, blood glucose, total cholesterol, triglyceride, temperature, onset, coexisting disease, gender, and Benson’s relaxation response. This observational analysis research uses cross-sectional design. The total number of subjects are 42 AIS patients that include 21 respondents in control group and 21 respondents in intervention group. The results of the study show that the level of Leukocyte p= 0.790; Blood Glucose p= 0.565; Total Cholesterol p= 0.982; Triglyceride p= 0.782; Temperature p= 0.50; Onset p= 0.028; Coexisting Disease p= 0.345; Sex p= 0.707; Benson’s Relaxation Response p= 0.019. Based on the results of the study, it is concluded that Onset and Benson’s Relaxation Response are significant factors in physiological response of AIS patients.